Hydrogen Sulfide and β-Synuclein Are Involved and Interlinked in the Aging Glaucomatous Retina. (14th April 2020) - Liu, Hanhan; Mercieca, Karl; Anders, Fabian; Prokosch, Verena
Abstract : Purpose . Glaucoma, one of the leading causes of irreversible blindness worldwide, is a group of disorders characterized by progressive retinal ganglion cell (RGC) loss. Synucleins, a family of small proteins, have been of interest in studies of neurodegeneration and CNS. However, their roles and functions in glaucoma are still not completely understood and remain to be explored. Our previous studies showed that α -synuclein and H2 S play a pivotal role in glaucoma. This study aims to (1) elucidate the potential roles and functions of synucleins in glaucoma throughout aging, (2) investigate the interaction between the synucleins and H2 S, and better understand the mechanism of H2 S in neuroprotection. Methods . The chronic IOP elevation model was carried out in 12 animals at different ages (3 months and 14 months), and RGCs were quantified by Brn3a staining. Mass spectrometric-assisted proteomics analysis was employed to measure synuclein levels and H2 S producing proteins in retina. Secondly, the acute IOP elevation model was carried out in 12 juvenile animals, with or without intravitreal injection of GYY4137 (a H2 S donor). RGCs were quantified along with the abundancy of synucleins. Results . RGCs and β -synuclein (SNCB) are significantly changed in old animals. Under chronic IOP elevation, there is a significant RGC loss in old animals, whereas no significant change in young animals; SNCB is significantly downregulated and 3MST is significantly upregulated in young animals due to IOP, while no significant changes in old ones are notable. Under acute IOP elevation (approx. 55 mmHg), a significant RGC loss is observed; exogenous H2 S significantly reduced RGC loss and downregulated SNCB levels. Conclusion . The present study indicates a strong link between ageing and SNCB regulation. In young animals SNCB is downregulated going along with less RGC loss. Furthermore, increasing endogenous H2 S is effective to downregulate SNCB and is neuroprotective against acute IOP elevation.